The 2001 Philippines yearbook facts and figures. ([Manila s.n.], 2001)
Contains Philippine government, diplomatic and media directories, listings of the top 5000 corporations in the country, the regions and provinces of the Philippines, and a services directory.
Keywords: Philippines -- Yearbooks; Philippines -- Directories